Porous composite gel as well as preparation method and application thereof in atmospheric catchment
By preparing a porous composite gel, combining polyvinyl alcohol foam gel with zwitterionic hydrogel and LiCl, a continuous three-dimensional macroporous network and multi-level channels are formed, which solves the problems of slow moisture absorption rate and inorganic salt loss, and achieves efficient moisture absorption and desorption performance, making it suitable for atmospheric water collection.
Patent Information
- Application Number
- CN202511473078.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2025-11-25
AI Technical Summary
Existing adsorption-type atmospheric water collection materials suffer from slow moisture absorption rate, low desorption efficiency, and loss of inorganic salts due to deliquescence, making it difficult to achieve multiple cycles of use.
A porous composite gel preparation method was adopted, which combines polyvinyl alcohol foam gel with zwitterionic hydrogel and hygroscopic salt LiCl to form a continuous three-dimensional macroporous network structure. LiCl was fixed by strong ion coordination to form multi-level channels to improve hygroscopic performance and cycle stability.
It significantly improves the moisture absorption rate and overall water capture efficiency. The material has a moisture absorption capacity of 2.9 g·g-1 at 90% relative humidity and maintains high-efficiency moisture absorption and desorption performance during the cycle, making it suitable for atmospheric water collection.
Smart Images

Figure CN121005949A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of atmospheric water collection, specifically relating to a porous composite gel for atmospheric water collection. Background Technology
[0002] With global population growth, accelerated urbanization, and continuously rising industrial water demand, traditional water resources are becoming increasingly strained, and freshwater shortages have become one of the major bottlenecks restricting social development in many regions. Water resources in the atmosphere, existing in the form of water vapor, are widely distributed and inexhaustible. Studies have shown that the annual water storage in the Earth's atmosphere is as high as approximately 129 trillion kilograms, far exceeding the total water storage of surface rivers. Therefore, atmospheric water harvesting technology, which directly extracts water from the atmosphere, has gradually attracted widespread attention from researchers, especially in remote areas without power grids or stable water sources, where it has broad application prospects.
[0003] Existing atmospheric water collection technologies mainly fall into three categories: condensation, adsorption, and hybrid. Condensation-based water collection devices primarily use a refrigeration system to cool the air below its dew point, causing water vapor in the air to condense into liquid water. This method is commercially available, but its operation relies on an external power system, resulting in high energy consumption and maintenance costs, making it unsuitable for long-term deployment in resource-constrained areas. In contrast, adsorption-based atmospheric water collection uses hygroscopic materials to adsorb moisture from the air under natural conditions, and then releases the adsorbed moisture through heating. This type of method has advantages such as low energy consumption, no need for complex equipment, and strong environmental adaptability, making it one of the key research directions currently.
[0004] In adsorption-type water-collecting materials, hydrophilic salts such as lithium chloride, calcium chloride, and magnesium chloride are widely used due to their excellent hygroscopic properties. However, these inorganic salt materials are prone to deliquescence, forming a liquid state after absorbing water, posing a risk of loss and making repeated recycling difficult. Hydrogel materials, due to their three-dimensional network structure, can effectively immobilize hygroscopic salts and prevent their loss, while also possessing a certain degree of water transport capacity and flexibility, making them ideal carriers for adsorption materials. However, traditional hydrogels have a dense structure, limiting water diffusion channels, resulting in slow adsorption rates and low desorption efficiency, affecting overall performance.
[0005] Patent document CN118480274A discloses a natural porous peat moss-based photothermal water-collecting material. This material involves mixing zwitterionic sulfobetaine hydrogel with hygroscopic salt LiCl and carbon black to form an interpenetrating polymer network, which is then added to cleaned, dried peat moss. The resulting water-collecting material is obtained through freeze-drying. The maximum water absorption capacity of this natural porous peat moss-based photothermal water-collecting material can reach 2.25 g / g. Summary of the Invention
[0006] In order to improve the moisture absorption performance of the existing water-collecting materials under 90% relative humidity conditions, the present invention provides a method for preparing a porous composite gel.
[0007] To achieve the above objectives, the present invention employs the following technical solution.
[0008] A method for preparing a porous composite gel, comprising: (1) Impregnate the polyvinyl alcohol foam gel with a solution containing [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide, an initiator and a crosslinking agent for a certain period of time; (2) The polyvinyl alcohol foam gel treated in step (1) is heated and polymerized for a certain time to obtain PVA / PDMAPS; (3) The PVA / PDMAPS were impregnated with lithium chloride solution for a certain period of time to obtain the porous composite gel.
[0009] Preferably, in the solution described in step (1), the concentration of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonylpropyl)ammonium hydroxide is 5-50 wt%, the concentration of the initiator is 0.05-2 wt%, and the concentration of the crosslinking agent is 0.01-2 wt%.
[0010] More preferably, the initiator is ammonium persulfate, and the crosslinking agent is N,N'-methylenebisacrylamide.
[0011] Preferably, the immersion in step (1) is carried out under ice bath conditions for 0.25 to 4 hours.
[0012] Preferably, the polymerization reaction in step (2) is carried out at a temperature of 20~80℃ and for a reaction time of 0.5~4 hours.
[0013] Preferably, the concentration of the lithium chloride solution in step (3) is 1~6 mol / L, and the immersion time is 1~72 hours.
[0014] Preferably, the foaming agent, acid, and crosslinking agent are added to a polyvinyl alcohol solution, and the solution is heated to foam and cure to obtain the polyvinyl alcohol foam gel.
[0015] More preferably, the heating and foaming temperature is 60~90℃, and the time is 3~10 hours.
[0016] More preferably, a foaming agent, an acid, a crosslinking agent, and a photothermal filler are added to a polyvinyl alcohol solution, and the solution is heated to foam and cure to obtain the polyvinyl alcohol foam gel.
[0017] Preferably, the foaming agent is n-hexane, the acid is sulfuric acid, the crosslinking agent is glutaraldehyde, and the photothermal filler is carbon black.
[0018] Preferably, the concentration of the polyvinyl alcohol solution is 5 to 20 wt%, more preferably, the concentration of the polyvinyl alcohol solution is 10 wt%.
[0019] More preferably, based on the mass of polyvinyl alcohol, the amount of foaming agent is 0.1~2 mL / g, the amount of acid is 0.005~0.05 mL / g, the amount of crosslinking agent is 0.001~0.1 mL / g, and the amount of photothermal filler is 0.005~0.05 g / g.
[0020] Most preferably, based on the mass of polyvinyl alcohol, the amount of foaming agent is 0.5 mL / g, the amount of acid is 0.01 mL / g, the amount of crosslinking agent is 0.015 mL / g, and the amount of photothermal filler is 0.015 g / g.
[0021] Porous composite gels prepared according to the above method.
[0022] The above-mentioned porous composite gel is used in atmospheric water collection.
[0023] In the composite gel material prepared in this invention, the continuous, interconnected three-dimensional macroporous network structure of the PVA foam gel provides a smooth mass transfer channel for efficient contact between the water and material interfaces, while ensuring rapid diffusion of water vapor within the material, effectively improving the moisture absorption rate and overall water capture efficiency. Secondly, after the zwitterionic hydrogel network is embedded in the PVA framework, a fine microporous structure is further generated within the macropores, forming a "multi-level pore structure." Its sulfonic acid groups (-SO3) - ) and quaternary ammonium group (-N + Functional groups such as (CH3)2 not only possess excellent hydrophilicity but also provide additional binding sites for water molecules through electrostatic interactions and hydrogen bonding effects. Simultaneously, this three-dimensional flexible network effectively anchors hygroscopic salt ions, restricting their migration and avoiding the deliquescence and loss problems common in traditional inorganic salts during hygroscopic processes, significantly enhancing cycle stability. Furthermore, LiCl hygroscopic salts exhibit superior performance. + The strong ionic coordination between the salt and the sulfonic acid groups on the hydrogel chains not only ensures stable salt loading but also promotes an increase in ion network density, enabling the material to maintain high-efficiency moisture absorption performance over a wide humidity range. Compared with the natural porous peat moss-based photothermal water collection material in CN118480274A, the porous composite gel of this invention achieves a moisture absorption capacity of 2.9 g·g at 90% relative humidity. -1 above. Attached Figure Description
[0024] Figure 1 These are Fourier transform infrared spectra of different materials.
[0025] Figure 2 Scanning electron microscope images of different materials.
[0026] Figure 3 The optical response properties of different materials.
[0027] Figure 4 This refers to the moisture absorption properties of different materials under different relative humidity conditions.
[0028] Figure 5 The adsorption-desorption cycle stability of DSFP-LiCl prepared in Example 1 at 50% relative humidity.
[0029] Figure 6 The temperature change curves (a) and desorption curves (b) of different materials under a single solar radiation intensity are shown. Detailed Implementation
[0030] The technical solution of the present invention will be further described in detail below with reference to the embodiments.
[0031] Example 1 10g of polyvinyl alcohol (PVA) was dissolved in 90mL of deionized water and heated and stirred until completely dissolved to obtain a 10wt% polyvinyl alcohol solution. Then, 5mL of n-hexane, 0.1mL of sulfuric acid (as a catalyst), 0.15mL of glutaraldehyde and 0.15g of carbon black were added. After stirring and mixing, the mixture was placed in an electric thermostatic drying oven at 85℃ for 6 hours to foam and cure, resulting in carbon black / PVA foam gel (named SFP). A zwitterionic [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propionic)ammonium hydroxide (DMAPS) was dissolved in water, and a certain amount of initiator (ammonium persulfate) and crosslinking agent (N,N'-methylenebisacrylamide) were added to prepare a homogeneous precursor solution (DMAPS 40wt%, initiator 1.0wt%, crosslinking agent 1.0wt%). Under ice bath conditions, SFP was immersed in this precursor solution for 1 hour for infiltration. After infiltration, the SFP was removed, heated to 60℃, and polymerized for 1 hour. After natural cooling, it was freeze-dried to obtain a carbon black / PVA / PDMAPS composite material (named DSFP). DSFP was immersed in a 4 mol / L lithium chloride solution for 48 hours, and then freeze-dried to obtain the final product DSFP-LiCl.
[0032] Comparative sample SFP-LiCl: SFP was immersed in a 4 mol / L lithium chloride solution for 48 hours, and then removed and freeze-dried.
[0033] Comparative sample PDMAPS: DMAPS was dissolved in water, and a certain amount of initiator (ammonium persulfate) and crosslinking agent (N,N'-methylenebisacrylamide) were added to prepare a homogeneous precursor solution (DMAPS 40wt%, initiator 1.0wt%, crosslinking agent 1.0wt%). The precursor solution was heated to 60℃ for polymerization reaction for 1 hour, and then freeze-dried after natural cooling.
[0034] Example 2 Dissolve 10g PVA in 90mL of deionized water, heat and stir until completely dissolved, then add 5mL of n-hexane, 0.1mL of sulfuric acid and 0.15mL of glutaraldehyde, stir and mix well, and place in an electric thermostatic drying oven at 85 ℃ for foaming and curing for 6 hours to obtain PVA foam gel (named FP). DMAPS was dissolved in water, and a certain amount of initiator (ammonium persulfate) and crosslinking agent (N,N'-methylenebisacrylamide) were added to prepare a homogeneous precursor solution (DMAPS 40wt%, initiator 1.0wt%, crosslinking agent 1.0wt%). FP was immersed in this precursor solution for 1 hour under ice bath conditions. After infiltration, FP was removed, heated to 60℃, and polymerized for 1 hour. After natural cooling, it was freeze-dried to obtain a PVA / PDMAPS composite material (named DFP). DFP was immersed in a 4 mol / L lithium chloride solution for 48 hours, and then freeze-dried to obtain the final product DFP-LiCl.
[0035] The following uses the materials prepared in Examples 1-2 and the comparative samples to characterize their properties.
[0036] Figure 1 These are Fourier transform infrared spectra of different materials. The characteristic peak of PVA is located at 2920 cm⁻¹. -1 (CH stretching), 1085 cm -1 (CO expansion) and 1720 cm -1 (C=O stretching of residual acetate groups). The characteristic peak of PDMAPS hydrogel is located at approximately 1180 cm⁻¹. -1 (S=O asymmetric stretching), 1030 cm -1 (SO3 - (Symmetrical stretching) and 1485-1610 cm -1 (CN stretching and N-CH3 bending) originate from its zwitterionic sulfobetaine structure. DSFP, on the other hand, fully retains the characteristic peaks of PVA and PDMAPS, including its OH stretching peak (~3430 cm⁻¹). -1The slight shift indicates that hydrogen bonding has formed between the PVA hydroxyl groups and the zwitterionic portion of the PDMAPS hydrogel. Compared with DSFP, the DSFP-LiCl spectrum shows significant changes: the S=O stretching peak broadens and shifts to 1182-1195 cm⁻¹. -1 SO3 - The symmetrical stretching peak shifted to approximately 1022 cm. -1 Meanwhile, the absorption peak in the CN region also showed a slight shift, and these changes directly confirmed that SO3 - With Li + Ion coordination was formed between the ions, and Cl - The presence of weak interactions between the ions and the quaternary ammonium groups indicates that LiCl has been successfully integrated into the PDMAPS hydrogel network.
[0037] Figure 2 Scanning electron microscope (SEM) images of different materials. SFP sample ( Figure 2 The DSFP exhibits a uniform and interconnected macroporous structure, providing unobstructed channels for rapid water vapor transport. After introducing zwitterionic hydrogel PDMAPS, the DSFP (… Figure 2 The DSFP-LiCl composite material further forms a uniformly distributed, dense micropore structure within the macropores, giving the material both the mass transfer advantages of macropores and the high specific surface area of micropores, thus significantly improving the effective contact area of the air-adsorption interface. After further impregnation with LiCl solution, the composite material DSFP-LiCl... Figure 2 The overall pore structure of the hydrogel remained stable, without significant collapse or damage, indicating that the hydrogel provided good fixation and support for the framework. Simultaneously, salt loading was observed on the pore surface, providing a physical basis for achieving efficient moisture absorption.
[0038] Figure 3 The optical response properties of different materials are compared. The introduction of carbon black significantly improves the optical response properties of the composite material. DFP-LiCl exhibits high reflectivity (50-60%) and certain transmittance (up to 50%) in the visible to near-infrared region (approximately 500-1000 nm), but its overall light absorption capacity is limited. In contrast, DSFP-LiCl achieves an absorption rate of over 85% in the 500-2500 nm wavelength range, with both reflectivity and transmittance approaching zero, demonstrating strong light absorption characteristics across almost the entire wavelength range.
[0039] Figure 4 The moisture absorption properties of different materials under different relative humidity conditions are shown. The moisture absorption of the base material FP at 30%, 50%, 70%, and 90% relative humidity are 0.014, 0.036, 0.081, and 0.100 g·g, respectively. -1It exhibits low moisture capture capacity. The moisture absorption of SFP after introducing carbon black is 0.030, 0.060, 0.120 and 0.157 g·g at the corresponding humidity levels. -1 Although the performance was improved compared to FP, the overall levels were similar, indicating that the main function of carbon black is photothermal conversion, with minimal impact on moisture absorption. Further introduction of the hygroscopic salt LiCl increased the moisture absorption of SFP-LiCl to 0.463, 0.750, 1.270, and 1.910 g·g, respectively. -1 The moisture absorption capacity of DSFP-LiCl was significantly higher than that of the undoped sample, indicating that LiCl played a dominant role in the moisture absorption process. However, some LiCl in SFP-LiCl tends to migrate or be lost after moisture absorption, limiting its cycling stability. In contrast, the moisture absorption capacity of DSFP-LiCl reached 0.630, 1.260, 1.740, and 3.190 g·g under relative humidity conditions of 30%, 50%, 70%, and 90%, respectively. -1 The moisture absorption capacities of DFP-LiCl were 0.580, 1.21, 1.673, and 2.964 g·g, respectively. -1 All of them are higher than SFP-LiCl.
[0040] Figure 5 The adsorption-desorption cycle stability of the DSFP-LiCl prepared in Example 1 was assessed at 50% relative humidity. It can be seen that after 10 cycles, the material still maintains a high moisture absorption capacity and stable desorption performance, exhibiting excellent cycle stability. This characteristic is of great significance for practical atmospheric water collection applications, as the material needs to withstand repeated wetting-drying processes without significant performance degradation during long-term continuous operation. Its stability mainly stems from three aspects: First, the zwitterionic hydrogel forms a uniform filling and effective support within the macroporous structure of the PVA foam, constructing a stable three-dimensional network framework, significantly enhancing the mechanical stability of the overall skeleton and avoiding performance degradation caused by structural collapse during cycling; second, the hydrogel and LiCl are bound together by strong ionic coordination bonds, firmly fixing the salt within the polymer network, thereby effectively inhibiting salt deliquescence and migration; third, the hydrophilic properties of the hydrogel itself provide a stable dispersion microenvironment for LiCl, which is beneficial for maintaining uniform salt distribution and preventing local aggregation. The synergistic effect of the above mechanisms ensures the continuous stability of the moisture absorption and desorption efficiency of the composite material during the cycling process, demonstrating excellent structural and functional durability.
[0041] Figure 6 The figures (a) and (b) show the temperature change curves and desorption curves of different materials under a single solar radiation intensity. Figure 6As shown in Figure a, after continuous irradiation under a certain solar intensity for 1 hour, the temperature rise of DSFP-LiCl and DFP-LiCl showed a significant difference. At 10 min, the temperature of DFP-LiCl was 45.7 ℃, while that of DSFP-LiCl had reached 58.6 ℃. By 60 min, the former's temperature was only 52.9 ℃, while the latter rose to 75.6 ℃ (the highest temperature of the natural porous peat moss-based photothermal water collection material of CN118480274A after irradiation under a certain solar intensity for 15 min can reach 55.9 ℃, while the temperature of DSFP-LiCl of this invention after irradiation under a certain solar intensity for 15 min can reach 60.4 ℃). The results indicate that carbon black photothermal additives possess abundant π-electron conjugated structures and surface defect states, enabling them to efficiently absorb incident light and rapidly convert it into heat energy through non-radiative relaxation processes. This significantly enhances the light absorption and photothermal conversion capabilities of the composite gel material, allowing it to accumulate heat more quickly and maintain a higher surface temperature. Furthermore, the multi-level pore structure of the composite gel material, with its multiple scattering and optical trapping effects, further extends the light propagation path within the material, enhancing the overall photothermal conversion capability and thus improving the material's ability to rapidly heat up under natural light conditions. Figure 6 As shown in b, DSFP-LiCl exhibits excellent desorption performance under different relative humidities: the desorption rates reach 0.73, 2.07, 2.95, and 3.08 kg·m³ at 30%, 50%, 70%, and 90% relative humidities, respectively. -2 ·h -1 Both exhibit highly efficient water release capabilities. Their excellent desorption behavior can be attributed to the efficient photothermal effect imparted by carbon black, which enables the material to heat up rapidly under solar irradiation and provide sufficient energy to drive water migration; at the same time, the porous PVA foam skeleton and zwitterionic hydrogel network together provide continuous water transport channels and salt fixation environment, ensuring the efficiency and reversibility of the desorption process.
[0042] Example 3 Dissolve 10g PVA in 90mL of deionized water, heat and stir until completely dissolved, then add 4mL of n-hexane, 0.2mL of sulfuric acid, 0.5mL of glutaraldehyde and 0.3g of carbon black, stir and mix well, and place in an electric thermostatic drying oven at 80℃ for 6 hours to foam and cure, thus obtaining carbon black / PVA foam gel (named SFP). DMAPS was dissolved in water, and a certain amount of initiator (ammonium persulfate) and crosslinking agent (N,N'-methylenebisacrylamide) were added to prepare a homogeneous precursor solution (DMAPS 50wt%, initiator 1.5wt%, crosslinking agent 1.5wt%). SFP was immersed in this precursor solution for 0.5 hours under ice bath conditions. After immersion, the SFP was removed, heated to 80℃, and polymerized for 0.5 hours. After natural cooling, it was freeze-dried to obtain a carbon black / PVA / PDMAPS composite material (named DSFP). DSFP was immersed in a 5 mol / L lithium chloride solution for 48 hours, and then removed and freeze-dried to obtain the final product DSFP-LiCl.
[0043] Example 4 Dissolve 10g of PVA in 90mL of deionized water, heat and stir until completely dissolved, then add 12g of PVA. 0.5 mL of hexane, 1.0 mL of sulfuric acid, 1.0 mL of glutaraldehyde and 0.4 g of carbon black were mixed and placed in a 90°C electric thermostatic drying oven for 6 hours to foam and cure, thus obtaining carbon black / PVA foam gel (named SFP). DMAPS was dissolved in water, and a certain amount of initiator (ammonium persulfate) and crosslinking agent (N,N'-methylenebisacrylamide) were added to prepare a homogeneous precursor solution (DMAPS 20wt%, initiator 0.5wt%, crosslinking agent 0.1wt%). SFP was immersed in this precursor solution for 3 hours under ice bath conditions. After infiltration, the SFP was removed and heated to 50℃ for polymerization reaction for 3 hours. After natural cooling, it was freeze-dried to obtain a carbon black / PVA / PDMAPS composite material (named DSFP). DSFP was immersed in a 6 mol / L lithium chloride solution for 24 hours, and then removed and freeze-dried to obtain the final product DSFP-LiCl.
[0044] Example 5 Dissolve 10g PVA in 90mL of deionized water, heat and stir until completely dissolved, then add 1mL of n-hexane, 0.05mL of sulfuric acid, 0.01mL of glutaraldehyde and 0.01g of carbon black, stir and mix well, and place in an electric thermostatic drying oven at 85℃ for 5 hours to foam and cure, thus obtaining carbon black / PVA foam gel (named SFP). DMAPS was dissolved in water, and a certain amount of initiator (ammonium persulfate) and crosslinking agent (glutaraldehyde N,N'-methylenebisacrylamide) were added to prepare a homogeneous precursor solution (DMAPS 40wt%, initiator 1.0wt%, crosslinking agent 1.0wt%). SFP was immersed in this precursor solution for 1 hour under ice bath conditions. After infiltration, the SFP was removed, heated to 60℃, and polymerized for 1 hour. After natural cooling, it was freeze-dried to obtain a carbon black / PVA / PDMAPS composite material (named DSFP). DSFP was immersed in a 1 mol / L lithium chloride solution for 72 hours, and then removed and freeze-dried to obtain the final product DSFP-LiCl.
[0045] Example 6 Dissolve 10g PVA in 90mL of deionized water, heat and stir until completely dissolved, then add 2mL of n-hexane, 0.1mL of sulfuric acid, 0.15mL of glutaraldehyde and 0.15g of carbon black, stir and mix well, and place in an electric thermostatic drying oven at 85 ℃ for 6 hours to foam and cure, thus obtaining carbon black / PVA foam gel (named SFP). DMAPS was dissolved in water, and a certain amount of initiator (ammonium persulfate) and crosslinking agent (glutaraldehyde) were added to prepare a homogeneous precursor solution (DMAPS 5wt%, initiator 0.05wt%, crosslinking agent 0.01wt%). SFP was immersed in this precursor solution for 4 hours under ice bath conditions. After infiltration, the SFP was removed and heated to 25°C for polymerization for 4 hours. After the reaction, it was freeze-dried to obtain a carbon black / PVA / PDMAPS composite material (named DSFP). DSFP was immersed in a 4 mol / L lithium chloride solution for 48 hours, and then freeze-dried to obtain the final product DSFP-LiCl.
[0046] Example 7 Dissolve 10g PVA in 90mL of deionized water, heat and stir until completely dissolved, then add 20mL of n-hexane, 0.5mL of sulfuric acid, 1mL of glutaraldehyde and 0.5g of carbon black, stir and mix well, and place in a 75℃ electric thermostatic drying oven for foaming and curing for 8 hours to obtain carbon black / PVA foam gel (named SFP). DMAPS was dissolved in water, and a certain amount of initiator (ammonium persulfate) and crosslinking agent (N,N'-methylenebisacrylamide) were added to prepare a homogeneous precursor solution (DMAPS 40wt%, initiator 1.0wt%, crosslinking agent 2.0wt%). SFP was immersed in this precursor solution for 1 hour under ice bath conditions. After infiltration, the SFP was removed and heated to 50℃ for polymerization reaction for 2 hours. After natural cooling, it was freeze-dried to obtain a carbon black / PVA / PDMAPS composite material (named DSFP). DSFP was immersed in a 1 mol / L lithium chloride solution for 48 hours, and then removed and freeze-dried to obtain the final product DSFP-LiCl.
[0047] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a porous composite gel, comprising: (1) Impregnate the polyvinyl alcohol foam gel with a solution containing [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide, an initiator and a crosslinking agent for a certain period of time; (2) The polyvinyl alcohol foam gel treated in step (1) is heated and polymerized for a certain time to obtain PVA / PDMAPS; (3) The PVA / PDMAPS were impregnated with lithium chloride solution for a certain period of time to obtain the porous composite gel.
2. The preparation method according to claim 1, characterized in that: In the solution described in step (1), the concentration of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonylpropyl)ammonium hydroxide is 5-50 wt%, the concentration of the initiator is 0.05-2 wt%, and the concentration of the crosslinking agent is 0.01-2 wt%. Preferably, the initiator is ammonium persulfate, and the crosslinking agent is N,N'-methylenebisacrylamide.
3. The preparation method according to claim 1, characterized in that: The immersion in step (1) is carried out under ice bath conditions for 0.25 to 4 hours.
4. The preparation method according to claim 1, characterized in that: The polymerization reaction in step (2) is carried out at a temperature of 20~80℃ and for a reaction time of 0.5~4 hours.
5. The preparation method according to claim 1, characterized in that: The lithium chloride solution concentration in step (3) is 1~6 mol / L, and the immersion time is 1~72 hours.
6. The preparation method according to claim 1, characterized in that: A foaming agent, acid, and crosslinking agent are added to a polyvinyl alcohol solution, and the solution is heated to foam and solidify to obtain the polyvinyl alcohol foam gel. Preferably, the heating and foaming temperature is 60~90℃.
7. The preparation method according to claim 6, characterized in that: A foaming agent, acid, crosslinking agent, and photothermal filler are added to a polyvinyl alcohol solution, and the solution is heated to foam and cure to obtain the polyvinyl alcohol foam gel.
8. The preparation method according to claim 7, characterized in that: The foaming agent is n-hexane, the acid is sulfuric acid, the crosslinking agent is glutaraldehyde, and the photothermal filler is carbon black; Preferably, based on the mass of polyvinyl alcohol, the amount of foaming agent is 0.1~2 mL / g, the amount of acid is 0.005~0.05 mL / g, the amount of crosslinking agent is 0.001~0.1 mL / g, and the amount of photothermal filler is 0.005~0.05 g / g; More preferably, the amount of foaming agent used is 0.5 mL / g, the amount of acid used is 0.01 mL / g, and the amount of crosslinking agent used is 0.015 mL / g, based on the mass of polyvinyl alcohol.
9. A porous composite gel prepared according to any one of claims 1 to 8.
10. The application of the porous composite gel according to claim 9 in atmospheric water collection.
Citation Information
Patent Citations
Composite moisture absorption material for adsorption type atmospheric water collection and preparation method and application thereof
CN116139831A
Preparation method of vertical porous high-efficiency air water collection composite gel
CN116253923A
Natural porous sphagnum-based photo-thermal water collection material and application thereof
CN118480274A
Hydrogel compound fabric with moisture absorption and retention performance and preparation method thereof
CN118932711A
Temperature-sensitive alkali-induced color-changing double-layer hydrogel as well as preparation method and application thereof
CN118978719A